Cryo-EM Structures and Regulation of Arabinofuranosyltransferase AftD from Mycobacteria - Tan, Yong Zi (Mol Cell, 2020)
Mycobacterium tuberculosis causes tuberculosis, a disease that kills over one million people each year. Its cell envelope is a common antibiotic target and has a unique structure due, in part, to two lipidated polysaccharides – arabinogalactan and lipoarabinomannan. Arabinofuranosyltransferase D (AftD) is an essential enzyme involved in assembling these glycolipids. We present the 2.9 Å resolution structure of M. abscessus AftD determined by single particle cryo-electron microscopy. AftD has a conserved GT-C glycosyltransferase fold and three carbohydrate binding modules. Glycan array analysis shows that AftD binds complex arabinose glycans. Additionally, AftD is non-covalently complexed with an acyl carrier protein (ACP). 3.4 and 3.5 Å structures of a mutant with impaired ACP binding reveal a conformational change suggesting ACP may regulate AftD function. Mutagenesis experiments using a conditional knock-out constructed in M. smegmatis confirm the essentiality of the putative active site and the ACP binding for AftD function.